Assessing the performance of hybrid CSP + PV plants in northern Chile. (15th November 2016) - Starke, Allan R.; Cardemil, José M.; Escobar, Rodrigo A.; Colle, Sergio
Highlights: Assessment of the hybridization between CSP and PV power plants. The existence of a size limit for integrating PV and PTC plants. Reducing the size of the CSP solar field, with high capacity factor and lower LCOE. Optimal tilt angle for the hybrid plant is higher than the one of a PV-only plant. Abstract: Electricity systems in Chile are characterized by a variable hourly demand in the central grid and an almost constant demand in the northern grid, which require different operation strategies for solar power plants depending on their location. Hybridizing a CSP plant with a PV system can increase the overall plant capacity factor by allowing thermal energy to be stored while the PV plant is in production and thus help to achieve a fully dispatchable solar electricity production system. A power generation and economic analysis of two hybrid CSP + PV plant models were developed considering a range of plant capacities based on parabolic trough or central receiver plants, combined with a PV system. Environmental conditions were considered for a site in the Atacama Desert, which is a hotspot of solar energy development in the country and shares the solar radiation characteristics of northern Chile. The study conducts a parametric analysis and optimization of the storage and power block sizes for the CSP plants in terms of the levelized cost of energy (LCOE), when the nominal capacity of the PV plant is varied. The annual production of the plants is calculated using the Transient System Simulation program (TRNSYS), which uses a new component library developed for that purpose. From the results of the simulations, the high potential for hybrid CSP + PV plants in the Atacama Desert is clear, because the high levels of irradiation available in northern Chile provide a competitive electricity cost, allowing investors to access PPA contracts at competitive prices and achieving competitive costs with respect to other energy sources.